Inhouse Bridging Thrombolysis Is Associated With Improved Functional Outcome in Patients With Large Vessel Occlusion Stroke: Findings From the German Stroke Registry - Maier, Ilko L.; Leha, Andreas; Badr, Mostafa; Allam, Ibrahim; Bähr, Mathias; Jamous, Ala; Hesse, Amelie; Psychogios, Marios-Nikos; Behme, Daniel; Liman, Jan (Frontiers in Neurology, 2021)
Background: Endovascular treatment (EVT) for large vessel occlusion stroke (LVOS) is highly effective. To date, it remains controversial if intravenous thrombolysis (IVT) prior to EVT is superior compared to EVT alone. Aim of our study was to specifically address the question, whether bridging-IVT directly prior to EVT has additional positive effects on reperfusion times, successful reperfusion and functional outcomes compared to EVT alone. Methods: Patients with LVOS in the anterior circulation eligible for EVT with and without prior IVT and direct admission to endovascular centers (mothership) were included in this multicentric, retrospective study. Patient data was derived from the German Stroke Registry (an open, multicenter and prospective observational study). Outcome parameters included groin-to-reperfusion time, successful reperfusion (defined as a Thrombolysis in Cerebral Infarction (TICI) scale 2b-3), change in National Institute of Health Stroke Scale (NIHSS), modified Rankin Scale (mRS) and mortality at 90 days. Results: Of the 881 included mothership patients with anterior circulation LVOS, 486 (55.2%) received bridging therapy with i.v.-rtPA prior to EVT and 395 (44.8%) received EVT alone. Adjusted, multivariate linear mixed effect models revealed no difference in groin-to-reperfusion time between the groups (48±36 vs. 49±34 min; p=0.299). Rates of successful reperfusion (TICI≥2b) were higher in patients with bridging-IVT (fixed effects estimate 0.410, 95% CI, 0.070; 0.750, p=0.018). There was a trend towards a higher improvement of the NIHSS during hospitalization (ΔNIHSS: bridging-IVT group 8 (IQR, 9.8) vs. 4 (IQR 11) points in the EVT alone group; fixed effects estimate 1.370, 95% CI, -0.490; 3.240, p=0.149). mRS at 90 days follow-up was lower in the bridging-IVT group (3 (IQR, 4) vs. 4 (IQR, 4); fixed effects estimate -0.350, 95% CI, -0.680; -0.010, p=0.041). There was a non-significantly lower 90-day mortality in the bridging-IVT group compared to the EVT alone group (22.4% vs. 33.6%; fixed effects estimate 0.980, 95% CI -0.610; 2.580, p=0.351). Rates of any intracerebral hemorrhage did not differ between both groups (4.1% vs. 3.8%, p=0.864). Conclusions: This study provides evidence that bridging-IVT might improve rates of successful reperfusion and long-term functional outcome in mothership patients with anterior circulation LVOS eligible for EVT.